Klausula Terkait Perlindungan terhadap Buruh Migran dan Urgensinya untuk Diatur Secara Khusus di dalam Perjanjian Perdagangan Bebas antara ASEAN dan Uni Eropa - Dodik Setiawan Nur Heriyanto (Jurnal Hukum IUS QUIA IUSTUM, 2015)
Economic globalization encourages some individuals to move abroad for a better living and livelihod. Currently, it is undeniable that the existence of foreign migrant workers can support the economic sutainability of European Union. However, foreign migrant workers mostly coming from ASEAN countries are only provided with limited social protection. Therefore, the research problems of this study are, first, whether the European Union rules have provided social protection for foreign migrant workers working around the territory or not? Second, what does ASEAN has to do in order to carry out its obligation to protect its citizens working outside ASEAN, especially within the framework of the agreement plan Free Trade Agreement between ASEAN and the EU? The research is conducted with normative method. The results of this study revealed two essential things: first, the rules in the European Union have not provided adequate protection for migrant workers of non-EU, especially for those coming from ASEAN countries. Secondly, there is the possibility for the inclusion of specific provisions related to social protection of migrant workers in the Free Trade Agreement between ASEAN and the EU.